EFFICACY AND SAFETY OF CHIMERIC ANTIGEN RECEPTOR-MODIFIED T CELL (CAR-T) THERAPY IN LYMPHOMA: AN UPDATED SYSTEMATIC REVIEW AND META-ANALYSIS - I Gede Krisna Arim Sadeva; I Gede Wikania Wira Wiguna; Ni Wayan Armerinayanti; Putu Mirah Wahyu Subagia Putri; Christo Timothy Mamangdean; Putu Ari Shanti Dewi; Kadek Meryndha Kumala Tungga; I Komang Raditya Putra Pratama; Agung Brahmanthya Nadine Kepakisan; Komang Indra Parama Arta (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2026)
Abstract Background: Lymphoma (Hodgkin and non-Hodgkin) is a malignancy of the lymphatic system, with global prevalence reaching 2.8% and mortality rates reaching 248,700 cases each year. Therefore, Chimeric Antigen Receptor-Modified T cell therapy (CAR-T) was developed as a new approach to improve survival rates in lymphoma patients. Objective: This study aimed to evaluate the efficacy and safety of CAR-T cell therapy in lymphoma. Methods: PRISMA 2020 was used in the literature search and systematic review with the keywords